Synthesis and characterization, electrical and gas sensing properties of N,N?-bis(salicylidene)-1,2-phenylendiamine substituted novel mono and ball-type metallo phthalocyanines - Yazici, Aysegul; Sarcicek, Bakiye; Altindal, Ahmet; Salih, Bekir; Bekaroglu, Ozer (Elsevier Science Sa, 2015)
The synthesis of 2,2'-{benzene-1,2-diylbis[nitrilo(E) methylidene]} phenol phenoxy phthalonitrile 1 and 2,2'-{benzene-1,2-diylbis[ nitrilo(E) methylidene]} diphenoxy diphthalonitrile 2 were achieved starting from N,N'-bis(salicylidene)-1,2-phenylenediamine, 4-nitrophthalonitrile and anhydrous K2CO3 in DMF at 70 degrees C under argon atmosphere. The template reaction of 1 with the corresponding metal salt gave the mono-nuclear zincphthalocyanine 3. The ball-type metallophthalocyanines 4 and 5 (Zn2Pc2 and LuPc2) were synthesized by starting from compound 2 with the corresponding metal salts heating in the medium without solvent. The compounds were characterized by elemental analysis, FT-IR, UV-Vis, MALDI-TOF mass and H-1 NMR spectroscopy techniques. Thin films of the compounds have been deposited by spin coating method on the glass substrate fitted with interdigitated gold electrodes. Electrical response of the films has been investigated by exposing the samples to various concentrations of SO2 gas. While exposure to SO2 has no influence on the electrical conductivity of compound 3, the conductivity of the films of 4 and 5 and strongly depend on the presence of this gas. Completely reversible sensor signals were obtained for these compounds with response and recovery times shorter than 2 min. and 40 s, respectively. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ball type; SO2 sensing; Dielectric; CBH model; Conductivity